Posterior short segment pedicle screw fixation and TLIF for the treatment of unstable thoracolumbar/lumbar fracture - Wang, Ling (BioMed Central, 2014)
BACKGROUND: Currently, Posterior Short Segment Pedicle Screw Fixation is a popular procedure for treating unstable thoracolumbar/lumbar burst fracture. But progressive kyphosis and a high rate of hardware failure because of lack of the anterior column support remains a concern. The efficacy of different methods remains debatable and each technique has its advantages and disadvantages. METHODS: A consecutive series of 20 patients with isolated thoracolumbar/lumbar burst fractures were treated by posterior short segment pedicle screw fixation and transforaminal thoracolumbar/lumbar interbody fusion (TLIF) between January 2005 and December 2007. All patients were followed up for a minimum of 2 years. Demographic data, neurologic status, anterior vertebral body heights, segmental Cobb angle and treatment-related complications were evaluated. RESULTS: The mean operative time was 167 minutes (range, 150–220). Blood loss was 450 ~ 1200 ml, an average of 820 ml. All patients recovered with solid fusion of the intervertebral bone graft, without main complications like misplacement of the pedicle screw, nerve or vessel lesion or hard ware failure. The post-operative radiographs demonstrated a good fracture reduction and it was well maintained until the bone graft fusion. Neurological recovery of one to three Frankel grade was seen in 14 patients with partial neurological deficit, three grades of improvement was seen in one patient, two grades of improvement was observed in 6 patients and one grade of improvement was found in 6 patients. All the 6 patients with no paraplegia on admission remained neurological intact, and in one patient with Frankel D on admission no improvement was observed. CONCLUSION: Posterior short-segment pedicle fixation in conjunction with TLIF seems to be a feasible option in the management of selected thoracolumbar/lumbar burst fractures, thereby addressing all the three columns through a single approach with less trauma and good results.